Threshold effect of inflation on economic growth in the West African Monetary Zone - Olorunsola E. Olowofeso; Maimuna John-Sowe; Santigie M. Kargbo; Adegoke Ibrahim Adeleke; Joseph R. Yengbe; Yaya Cham (West African Monetary Institute (WAMI), 2022)
While previous studies have explored the relationship between inflation and economic growth, the existing literature on threshold effect of inflation on economic growth in the West African Monetary Zone (WAMZ) predominantly assumes a linear association, neglecting the possibility of nonlinearity. This study aims to fill the gap in the empirical literature by exploiting the variation in inflation rates across countries and over time to identify endogenously the threshold inflation level that affects economic growth in WAMZ countries over the period 2001-2019. The paper applies a Panel Smooth Transition Regression (PSTR) model, considering the heterogeneity in inflation rates across countries and over time and nonlinearities in the inflation-growth nexus. Results reveal an inflation threshold of 10.3 per cent per annum for WAMZ countries, showing that achieving moderate inflation below this threshold will stimulate economic growth while high inflation above the threshold is detrimental to growth. The result provides strong empirical support for the policy stance of WAMZ countries regarding the convergence criterion to contain inflation to a single-digit level. This finding highlights the importance of adopting moderate inflation target below the identified threshold of 10.3 percent to foster sustainable economic growth. It underscores the need for central banks to adopt more proactive approach to monetary policy by closely monitoring inflation levels and taking appropriate actions to keep inflation within this desired range. Indeed, the evidence of such a nonlinear relationship implies that central banks should pay close attention to managing inflation expectations, through measures including clear and effective communication of monetary policy actions, which would help anchor inflation expectations to ensure a favourable inflation environment that supports economic growth and improve credibility of monetary policy in the region.
Keywords: E31; O47; C34; 330; Inflation; Growth; Threshold Effects; West Africa